Update on surgical management of enteroatmospheric fistulae in intestinal failure patients. Issue 2 (31st January 2022) - Nikoupour, Hamed; Theodorou, Alexis; Arasteh, Peyman; Lurje, Georg; Kalff, Joerg C.; von Websky, Martin W.
Abstract : Purpose of review: The surgical management of enteroatmospheric fistula (EAF) in patients with intestinal failure represents a major challenge for a surgical team and requires proficiency in sepsis management, nutritional support and prehabilitation, beside expertise in visceral and abdominal wall surgery. This review provides an update on the current recommendations and evidence. Recent findings: Reconstructive surgery should be performed at a minimum of 6–12 months after last laparotomy. Isolation techniques and new occlusion devices may accelerate spontaneous EAF closure in selected cases. Chyme reinfusion supports enteral and parenteral nutrition. Stapler anastomosis and failure to close the fascia increase the risk of EAF recurrence. Posterior component separation, intraoperative fascial tension and biological meshes may be used to accommodate fascial closure. Summary: Timing of reconstructive surgery and previous optimal conservative treatment is vital for favorable outcomes. Wound conditions, nutritional support and general patient status should be optimal before attempting a definitive fistula takedown. Single stage procedures with autologous gut reconstruction and abdominal wall reconstruction can be complex but well tolerated.